Rolnicy ekologiczni o szansach i zagrożeniach swoich gospodarstw - Łuczka-Bakuła, Władysława (Wydział Prawa i Administracji UAM, 1995)
The paper discusses the results of a research carried out in 1994 in which farms producing crops in a ecological form were analysed. The research was to identify the opportunities and threats brought about by the implementation of new production methods on farms. The results show that 75% of the respondents have taken the risk to produce food in a ecological form. Out of those 38% do it to be competitive in the Polish market, and 33% have done so to compete with foreign food producers. Only 25% of the farmers decide to produce crops in a ecological way because they want to use production means better. The most frequently quoted threats were: lack of interest in natural food among consumers (72%) and instable sales structure for that type of product (69%). Other threats included a decline in income (33%) and a demand barriers caused by high prices of natural food (29%). The economic situation of ecological farms is not uniform and depends on the attitude of a given farmer to the requirements of the market. Pro-market attitudes account for about 30% of all farmers. Those farmers follow active business strategy and present optimistic views on the future chances of healthy food and the potential income growth resulting from increased sales of such products. The others see their income growth as dependent on a number of different, sometimes quite extensive, forms of state's assistance.
Ecological forms of farming - opportunities and threats